Solution of Nonlinear Volterra Integral Equations with Weakly Singular Kernel by Using the HOBW Method - Mohamed R. Ali; Mohamed M. Mousa; Wen-Xiu Ma (Advances in Mathematical Physics)
We present a new numerical technique to discover a new solution of Singular Nonlinear Volterra Integral Equations (SNVIE). The considered technique utilizes the Hybrid Orthonormal Bernstein and Block-Pulse functions wavelet method (HOBW) to solve the weakly SNVIE including Abel’s equations. We acquire the HOBW implementation matrix of the integration to derive the procedure of solving these kind integral equations. The explained technique is delineated with two numerical cases to demonstrate the benefit of the technique used by us. At last, the exchange uncovers the way that the strategy utilized here is basic in usage.